2011
DOI: 10.1111/j.1600-0560.2011.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and survival of desmoplastic melanoma in the United States, 1992-2007

Abstract: The incidence of DM has been increasing steadily over the past 15 years. Older age, anatomic site of the head and neck, tumor thickness >2 mm, ulceration, lymph node involvement and non-receipt of surgery are associated with lower survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 37 publications
8
90
0
2
Order By: Relevance
“…Thus, our results are in accordance with other studies that have reported a link between DM, chronic actinic damage, and LM. 2,3 We speculate that mDM is more likely to have risk factors and clinical and phenotypic characteristics similar to those of LM. In contrast to DM, desmoplastic nevus appears to be associated with younger age and development on non-sunexposed areas.…”
mentioning
confidence: 95%
“…Thus, our results are in accordance with other studies that have reported a link between DM, chronic actinic damage, and LM. 2,3 We speculate that mDM is more likely to have risk factors and clinical and phenotypic characteristics similar to those of LM. In contrast to DM, desmoplastic nevus appears to be associated with younger age and development on non-sunexposed areas.…”
mentioning
confidence: 95%
“…1 Features unique to this melanoma type include delayed diagnosis, deep invasion, increased perineural invasion and local recurrence. 2,3 George et al 4 recently reviewed 87 cases of desmoplastic melanoma and identified a significant difference in propensity for regional lymph node metastasis in the variant composed of a mixed population of cells, that is, cells resembling conventional melanoma in addition to spindled cells, compared with the variant composed predominantly of spindled cells, lending credence to the concept of subclassifying desmoplastic melanoma into mixed and pure subtypes.…”
mentioning
confidence: 99%
“…The median age of DM cases is approximately 60 years, and it is about 10 years later than that of conventional melanoma. [2] Besides DM occurs more often in men, and a maleto-female ratio is 2.3 in the United States. [2] It has a predilection for sun-damaged skin, and about 50% of DM are found on the head and neck, including face, ears, and scalp.…”
Section: Cutaneous Combined Desmoplastic Melanomamentioning
confidence: 99%